Analisis Efisienisi Teknis Usahatani Ubi Kayu di Kabupaten Lampung Tengah - Andarwangi, Tunjung; Pratiwi, Dita; Bellapama, Intan Andya; Fajri, Ratu Chaterine; Budiman, Valdi Mughni (Universitas Galuh, 2026)
Central Lampung Regency is one of the cassava production centers in Lampung Province, which has vast land potential and a climate that supports the development of cassava farming. Cassava production in Central Lampung ranks highest in terms of food production compared to five other potential food commodities, namely corn, soybeans, sweet potatoes, and peanuts. High production does not guarantee high profits for cassava farmers. This study aims to analyze the factors that influence cassava production, the elasticity and scale of cassava farming, as well as the technical and allocative efficiency of cassava farming in Central Lampung Regency. The research was conducted in two subdistricts, namely Seputih Mataram and Terbanggi Besar, using a survey method and random sampling of 60 farmers. The data were analyzed using the Cobb-Douglass production function model and then using the Stochastic Frontier Analysis (SFA) tool. The results showed that the factors that significantly influenced cassava production were land area, phonska fertilizer, and organic fertilizer, while seeds, urea fertilizer, pesticides, and labor had no significant effect. The average technical efficiency value of 0.8595 indicates that cassava farming is fairly efficient. Age and land ownership status were found to reduce technical inefficiency, while experience, education, and access to credit had no significant effect. The production scale value of 0.814953 indicates decreasing returns to scale, which means that additional inputs no longer increase output proportionally.